SERUAN DAKWAH RASULULLAH SAW DALAM SURAT-SURAT (KAITANNYA DENGAN AGAMA: SERUAN KEPADA UMAT ISLAM DAN UMAT KAFIR) - KAJIAN STILISTIKA - Rachman, Solahuddin Abdul (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2025)
This study examines the call to da'wah of the Prophet PBUH contained in his letters through a stylistic approach, focusing on the call addressed to Muslims and infidels. Da'wah is one of the main missions of the Prophet PBUH which is not only carried out orally, but also through writing in the form of letters sent to various leaders and communities at that time. The research method used is stylistic analysis with a descriptive-qualitative approach to the text of the letters of the Prophet PBUH which contain the call to da'wah. The analysis focused on the language style, word choice, sentence structure, and rhetorical strategies used in conveying the message of da'wah to two different target groups: Muslims and infidels. The results of the study show that the Prophet PBUH used a different stylistic approach in preaching to Muslims and infidels. In the appeal to Muslims, the language style used tends to be persuasive-educational with an emphasis on strengthening faith, reminding of religious obligations, and motivation to increase piety. Meanwhile, in his appeal to the infidels, the Prophet PBUH used a more diplomatic but firm approach, with an emphasis on the invitation to convert to Islam, an explanation of the oneness of Allah, and a warning of the consequences of rejecting the truth. This stylistic difference reflects the wisdom of the Prophet PBUH in choosing the right communication strategy according to the background and psychological condition of the message recipient. These findings contribute to the understanding of the da'wah method of the Prophet PBUH and its relevance for the development of contemporary da'wah strategies